SISTEM INFORMASI OLEH-OLEH KHAS BENGKULU PADA TOKO AKILAH 2R - Julia Mayang Sari; Widhia KZ Oktoeberza (Rekursif: Jurnal Informatika, 2026)
Akilah 2R is a Bengkulu traditional souvenir store that previously managed product, stock, and transaction data manually, which caused data inaccuracies and delays in reporting. This study aims to develop a web-based information system that covers both admin and user sides to support digital store management. The admin is provided with features to manage products, categories, tags, orders, deliveries, and to generate sales reports automatically. Meanwhile, users are able to browse product catalogs, place orders, and monitor their order status online. The system was developed using the prototyping method and tested using black box testing. The results show that the system improves data management efficiency, accelerates transaction processing, and provides convenience for customers in ordering products through the website. Keywords: Information System, E-Commerce, Laravel Framework, Web-Based Application, Akilah 2R